A Panel Data Test of the Bank Lending Channel in Sweden - Joakim Westerlund (Lund University, School of Economics and Management, Department of Economics, 2003)
In this paper, we test the bank lending channel of monetary policy transmission in Sweden. Using a panel of bank balance sheet data covering the period 1998:M1 to 2003:M6, we test for bank loan supply shifts by segregating banks by asset size, liquidity and capitalization. The main result is that small, illiquid and undercapitalized banks are significantly affected by monetary policy, which supports the hypothesis of the bank lending channel
Keywords: C33; E42; E52; E52; F42; G21; 330; Monetary Transmission; Bank Lending Channel